Effects of estradiol cypionate dosage and body condition on reproductive performance of Nellore cattle synchronized for timed-artificial insemination - Sales, A.; Cappellozza, B. I.; Vilela, E.; Claro Júnior, I.; Sá Filho, O. G.; Vasconcelos, J. L.M. [UNESP] (Elsevier, 2023)
This experiment was designed to evaluate the effects of increasing doses of estradiol cypionate (ECP) and different body condition score (BCS) on reproductive performance of Bos indicus beef females assigned to a timed-artificial insemination (TAI) management. In this experiment, 1683 Bos indicus Nellore cows were blocked by parity and assigned to receive 1) an intravaginal P4 device (1.9 g of P4) and 2.0 mg of estradiol benzoate on day −11, 12.5 mg (i.m.) of dinoprost tromethamine, 300 IU (i.m.) of equine chorionic gonadotrophin, 0.6 mg (i.m.) of estradiol cypionate and CIDR withdrawal on day −2, followed by TAI on day 0 (n = 849; 0.6ECP) or 2) the same synchronization protocol with 1.0 mg of ECP on day −2 (n = 834; 1.0ECP). In both treatments, estrus expression was measured between days −2 and 0. Body condition score (BCS) was evaluated on days −11, 31, and 71 of the experiment and the BCS variation (Δ) was also determined between these timepoints. Transrectal ultrasonography was performed on days 31, 71, and 111 for pregnancy rate determination. All binary data were analyzed using cow as the experimental unit with GLIMMIX, whereas continuous variables were analyzed with the MIXED procedure of SAS. No treatment effects were observed on estrus expression rate. Treatment × BCS interactions were observed for pregnancy rates in all time points (days 31, 71, and 111), as 1.0ECP cows with a LOW BCS also had a greater P/AI than cows assigned to 0.6ECP. In summary, increasing the dose of ECP benefited the reproductive performance of Nellore beef cows with a reduced BCS (≤2.75), whereas no benefits were seen when the BCS was considered adequate (>2.75).
Keywords: Beef females; Body condition score; Estradiol cypionate; Estrus expression; Pregnancy rate